2021
DOI: 10.1097/scs.0000000000007421
|View full text |Cite
|
Sign up to set email alerts
|

A Posterior Rotational Flap Technique Using Distraction Osteogenesis for Unilateral Lambdoid Craniosynostosis

Abstract: Introduction:The craniofacial asymmetry seen in unilateral lambdoid craniosynostosis may not be effectively treated by posterior cranial vault remodeling, endoscopic suturectomy, and helmet therapy, or suturectomy and distraction osteogenesis alone due to limitations in soft-tissue envelope expansion and relapse of the deformity. The authors report a series of unilateral lambdoid craniosynostosis patients treated with a posterior rotational cranial-flap technique using internal distraction osteogenesis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In addition, they showed that the posterior ration flap technique provides a sufficient increase in intracranial volume, and our method is comparable with their study. The bone flap in our method was slightly smaller than that in their study, and the location of the valve was localized near the occipital region 8. Barrel stave osteotomy (case 2 only) and back cutting were added to increase intracranial volume, and an absorbable plate was used to reinforce the hinge area.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, they showed that the posterior ration flap technique provides a sufficient increase in intracranial volume, and our method is comparable with their study. The bone flap in our method was slightly smaller than that in their study, and the location of the valve was localized near the occipital region 8. Barrel stave osteotomy (case 2 only) and back cutting were added to increase intracranial volume, and an absorbable plate was used to reinforce the hinge area.…”
Section: Discussionmentioning
confidence: 94%
“…Kamel et al8 reported the use of a posterior rotation flap technique during the distraction osteogenesis of ULS. The increase in intracranial volume was considered sufficient in this report.…”
Section: Discussionmentioning
confidence: 99%
“…(Fig. 4) Gradual, incremental expansion of the suture gap and preservation of dura-bone attachments with DO was hypothesized to more naturally simulate in-vivo cranial growth and minimize bone resorption, leading to improved long-term esthetic outcomes compared with traditional open approaches 6,15–19. (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, DO utilizing a posterior rotational cranial flap has become the technique of choice for treating ULS. 6 This technique begins with the patient placed in a prone position. A bicoronal flap is first elevated in a subgaleal plane beyond the nuchal ridge.…”
Section: Operative Techniquementioning
confidence: 99%
See 1 more Smart Citation